2014
DOI: 10.1371/journal.pone.0110071
|View full text |Cite|
|
Sign up to set email alerts
|

Running the Gauntlet: Regional Movement Patterns of Manta alfredi through a Complex of Parks and Fisheries

Abstract: Manta rays (Genus Manta) are economically important for fisheries and tourism in Indonesia. These species have been listed by the International Union for the Conservation of Nature Red List as Vulnerable to extinction; therefore, human exploitation of manta rays must be regulated. A better understanding of the habitat use and movement patterns of manta rays in Indonesia is needed in order to employ effective conservation measures. To gain better insight into the movements of Manta alfredi we used ‘Manta Matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 24 publications
(73 reference statements)
5
70
0
Order By: Relevance
“…However, recent studies have blurred the proposed ecological characteristics that define the movements and habitat selection of the two species (Kashiwagi et al, 2011). For example, while reef manta rays are predominantly resident, they also undertake occasional long-distance movements of several hundred kilometers (Germanov and Marshall, 2014;Jaine et al, 2014;Braun et al, 2015). Further, reef manta rays access both coastal habitats and offshore, pelagic habitats where they are presumably foraging Jaine et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have blurred the proposed ecological characteristics that define the movements and habitat selection of the two species (Kashiwagi et al, 2011). For example, while reef manta rays are predominantly resident, they also undertake occasional long-distance movements of several hundred kilometers (Germanov and Marshall, 2014;Jaine et al, 2014;Braun et al, 2015). Further, reef manta rays access both coastal habitats and offshore, pelagic habitats where they are presumably foraging Jaine et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The near‐continuous distribution for M. alfredi raises questions about regional population structure. It is well‐established that M. alfredi exhibits strong migratory behaviour and movements of up to 500 km are not uncommon (Couturier et al ., ; Germanov & Marshall, ; Jaine et al ., ), with few confirmed dispersals in Australia up to 1150 km (Armstrong et al ., ). Individual rays have demonstrated affinity for particular sites and regions (Braun et al ., ; Couturier et al ., ; Kessel et al ., ; Marshall et al ., ), although most photo‐ID and tagging studies have focused on populations separated by large distances and/or by regions of deep water (Deakos et al ., ).…”
Section: Collated Sightings For M Alfredi and M Birostris In Austramentioning
confidence: 97%
“…These currents influence the southern range of various mobile species (Couturier et al, 2011;Dudgeon et al, 2013;Payne et al, 2018), with many tropical marine species reaching their southern range limit, and many temperate species reaching their northern limit, at latitudes of~25 S to~30 S on Australiaʼs east and west coastlines (Blair et al, 2014;Gomon et al, 2008;Last & Stevens, 2009 The near-continuous distribution for M. alfredi raises questions about regional population structure. It is well-established that M. alfredi exhibits strong migratory behaviour and movements of up to 500 km are not uncommon (Couturier et al, 2011;Germanov & Marshall, 2014;Jaine et al, 2014), with few confirmed dispersals in Australia up to 1150 km . Individual rays have demonstrated affinity for particular sites and regions (Braun et al, 2015;Couturier et al, 2014;Kessel et al, 2017;Marshall et al, 2011), although most photo-ID and tagging studies have focused on populations separated by large distances and/or by regions of deep water (Deakos et al, 2011).…”
mentioning
confidence: 99%
“…The near-continuous distribution for M. alfredi raises questions about regional population structure. It is well-established that M. alfredi exhibits strong migratory behaviour, with movements of up to 500 km not uncommon (Couturier et al 2011, Germanov and Marshall 2014, Jaine et al 2014) and recently movements of at least 1150 km have been demonstrated (Armstrong et al 2019). Photo-identification and tagging studies show that individual rays have an affinity for particular sites and regions (Braun et al 2015, Couturier et al 2014, Kessel et al 2017, Marshall et al 2011).…”
Section: Discussionmentioning
confidence: 99%